Modoc : the true story of the greatest elephant that ever lived - Helfer, Ralph (HarperPerennial, 1998)
On a quiet morning in 1896, in a small German circus town, a boy and an elephant were born. The boy was named Bram, the elephant was named Modoc. Bram was the son of a local elephant handler, and even as a child he showed signs of becoming a master handler. Modoc grew impressively beyond anyone's imagination--exceptional intelligence, massive size, and a gentleness surpassing that of even the kindest elephants. The two were raised as siblings, and when news came that the circus was being sold, thirteen-year-old Bram did the only thing he could imagine: he stowed away to be with Modoc.